Gender and age bias in immune competence and oxidative stress markers in Murrah buffaloes - PAMPORI, Z A; PANDITA, S (The Indian Journal of Animal Sciences, 2013)
Present study was carried out in Murrah buffaloes to recognise variability in basic circulatory levels of various immune response mediators or oxidative stress markers between sexes, ages and estrous cycle stages. Lymphocyte proliferation and plasma IgG varied between age groups and stages of estrous cycle. Lymphocyte proliferation wasnegatively correlated whereas plasma IgG levels were positively correlated with age. Plasma nitric oxide and tumornecrosis factor Î± was sex biased. Significantly low levels of NO and TNFÎ± were recorded in diestrous than estrous buffaloes. Xanthine oxidase did not differ between sexes or stages of reproductive cycle. Total leukocytes were higher in prepubertal and at estrus as compared to post pubertal and at diestrous buffaloes. TBARS registered increase with age and was predominant in females at diestrous. Antioxidant power was high in females than males but low in postpubertal buffaloes. Present findings make out the apparent role of age and sex steroids in immune competence.